Penggunaan Aplikasi Duolingo Dalam Meningkatkan Penguasaan Kosakata Berbahasa Inggris Siswa SMP Amalyatul Huda - Juliana, Juliana; Suci Amaniarsih, Dwi; Aqsal Ilham, Muhammad (Publikasi Pengabdian Masyarakat, 2023)
The ability to communicate using English is very important in supporting English language learning. Duolingo application is an application that is very helpful in providing new experiences for students to be directly involved in learning activities. Duolingo application effectively increases students’ vocabulary mastery with features and online tests that support students’ vocabulary mastery. Target of this service activity is students of Amalyatul Huda Junior High School. Method of implementing activities is through delivery of material and usage of Duolingo and then doing tests. Results indicated that there was an increase in students' vocabulary mastery using Duolingo application through questionnaires and test. Questionnaire results show that 92% of students understood to use Duolingo application. Students' test results show that average score of students' vocabulary mastery is 80 points. From results, it can be concluded that the use of Duolingo application can improve students’ vocabulary mastery of Amalyatul Huda Junior High School.